DEVELOPMENT OF A MOBILE APPLICATION FOR REMINDER ABOUT TAKING MEDICINES - Алтухова, Тетяна; Сергієнко, Людмила; Сергієнко, Олександр (SWorldJournal, 2025)
The article deals with the issue of developing a convenient and functional mobile application that provides management of reminders for timely medication. The main aspects of the subject area are considered, the choice of technologies is substantiated, th